Peran pendidikan karakter dalam membangun identitas naional di era globalisasi - Evrilita, Zaskia (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the role of character education in building national identity in the era of globalization, as well as the challenges faced. The era of globalization with technological advances and easy access to information presents challenges to national identity due to the rapid influence of foreign cultures. Character education based on the values of Pancasila and Indonesian culture to instill awareness of nationalism, togetherness in diversity, tolerance, and concern in the younger generation. This study shows that character education plays an important role in maintaining balance in the era of globalization, protecting national identity, and building a strong national identity. This study also suggests strong cooperation between schools and the community in optimizing the instillation of national values through character education by positive activities that foster a spirit of nationalism.